Modified alvarado scoring system. How much helpful? - Rassam, Raid E. (AL-Kindy College Medical Journal, 2012)
Background:-The Modified Alvarado Scoring System (MASS) has been reported to be a cheap and quick diagnostic tool in patients with acute appendicitis. However, differences in diagnostic accuracy have been observed if the scores were applied to various populations and clinical settings. Objectives:- The purpose of this study was to evaluate the diagnostic value of Modified Alvarado Scoring System in patients with acute appendicitis in our setting. Methods:-one hundre twenty eight patients ,were included in this study, admitted to Al-Kindy teaching hospital from June 2009 to June 2010. Patients’ age ranged from 8 to 56 years (21±10) they were divided into three groups; paediatrics, child bearing age females & adult males,. MASS was calculated for each patient included as the diagnosis & treatment were done on the bases of surgeon’s clinical decision,confirmation was done by histopathological examination. Finally statistics done included negative appendectomy rate, sensitivity,specificity,positive predictive value,negative predictive value & accuracy. Results:- Our negative appendectomy rate was 19.5% (22.22% for paediatrics 40.9% for females 4.2% for males). MASS showed sensitivity of 61%(92.8% for paediatrics 38% for females & 58% for males), specificity 80% (75% for paediatrics 88% for females & 50% for males), positive predictive value 92%(92.8% for paediatrics 83% for females 50% for males), negative predictive value 33% ( 75%for paediatrics 50% for females 5% for males) & accuracy 65% ( 88.9% for paediatrics 59% for females 58% for males). Conclusion:- MASS was of limited help to junior doctors in our setting,clinical assessment & experience are still the gold standard for acute appendicitis.